2013
DOI: 10.1016/j.yjmcc.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates cardiac fibroblast migration via the differential regulation of matrixins and RECK

Abstract: Sustained induction and activation of matrixins (matrix metalloproteinases or MMPs), and the destruction and deposition of extracellular matrix (ECM), are the hallmarks of cardiac fibrosis. The reversion-inducing-cysteine-rich protein with Kazal motifs (RECK) is a unique membrane-anchored endogenous MMP inhibitor. We hypothesized that elevated angiotensin II (Ang II), which is associated with fibrosis in the heart, differentially regulates MMPs and RECK both in vivo and in vitro. Continuous infusion of Ang II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 48 publications
9
96
0
Order By: Relevance
“…Therefore, we speculate that Ang II induces the synthesis and secretion of collagens I and III via the AP1 activation pathway. Further evidence suggests that ERK1/2 signaling is primarily responsible for Ang IIinduced AP1, collagen I, and collagen III expression (29). In this study, we found that expression of the pERK1/2 protein was upregulated in the Ang II group compared to the control group.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we speculate that Ang II induces the synthesis and secretion of collagens I and III via the AP1 activation pathway. Further evidence suggests that ERK1/2 signaling is primarily responsible for Ang IIinduced AP1, collagen I, and collagen III expression (29). In this study, we found that expression of the pERK1/2 protein was upregulated in the Ang II group compared to the control group.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that DHA inhibits angiotensin II-induced migration in cardiac fibroblasts by inducing reversion-inducing cysteine-rich protein with Kazal motifs (RECK) (33). Since angiotensin II inhibits RECK expression and RECK inhibits release and activation of metalloendopeptidase MMP2 (32), which triggers migration, reversal of angiotensin II-induced RECK suppression by DHA seems to be a key mechanism. DHA has also been reported to inhibit IL-1β-induced migration of rat VSMCs and suppress IL-1β-induced MMP2 as well as MMP9 via mechanisms involving DHA-induced Notch signaling pathways (4).…”
Section: Methodsmentioning
confidence: 99%
“…All data were normalized to corresponding hprt (hypoxanthine phosphoribosyltransferase) levels and analyzed using the 2 Ϫ⌬⌬Ct method. Activation of MMP2 and -9 was analyzed by immunoblotting using antibodies that detect both pro and active forms (MMP2, NB200 -114G, Novus; MMP9, M9570, Sigma) (58).…”
Section: Methodsmentioning
confidence: 99%